2018
DOI: 10.4081/ejh.2018.2866
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of sudden cardiac death due to early myocardial ischemia: An ultrastructural and immunohistochemical study

Abstract: The aim of this post-mortem ultrastructural and immunohistochemical study is to explore the characteristics of acute myocardial ischemia in the context of sudden death, using the combination of two different methods, both more insightful than ordinary histology. Transmission electron microscopy and immunohistochemistry, in addition to the traditional histology, were applied to study human heart specimens collected during forensic autopsies. The whole series was sub-grouped into cases (n=17) and controls (N=10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
1
13
0
2
Order By: Relevance
“…Formalin-Fixed Paraffin-Embedded (FFPE) LV tissue from a CMP patient with a LARGE1 promoter variant and controls without LARGE1 variants were used for IHC analysis using standard techniques 116 . FFPE tissue blocks were sectioned at 4 μ m, dewaxed in xylene, dehydrated with a serial dilution of ethanol solution and washed with PBS.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Formalin-Fixed Paraffin-Embedded (FFPE) LV tissue from a CMP patient with a LARGE1 promoter variant and controls without LARGE1 variants were used for IHC analysis using standard techniques 116 . FFPE tissue blocks were sectioned at 4 μ m, dewaxed in xylene, dehydrated with a serial dilution of ethanol solution and washed with PBS.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Various studies have shown that remodeling of connexin expression and gap junction organization occurs in adult heart conditions such as arrhythmia, ischemic heart disease, and sudden cardiac death ( Severs et al, 2008 ; Molina et al, 2018 ; Visoná et al, 2018 ). Alterations can occur in the distribution, amount, and type of connexin expression during different types of heart disease in humans.…”
Section: Absorptionmentioning
confidence: 99%
“…The ultrastructural morphological approach at TEM has been widely used in basic and applied biomedical research for the study of different tissues under unperturbed or experimental conditions: tooth structure and repair; 47 , 48 white adipose tissue classification; 49 , 50 stem cells culture for reconstructive purpose; 51 , 52 skeletal muscle features under experimental 53 , 54 and pathological 55 , 56 conditions; liver response to pretransplantation treatment; 57 female reproductive organs 58 and explanted oocytes for in vitro reproduction; 59 , 60 post-implant skin modification; 61 autopsy myocardium for diagnostic purposes 62 .…”
Section: May Electron Microscopy Still Make a Relevant Contribution Tmentioning
confidence: 99%